Interface-Driven Software Requirements Analysis - Ahmad, Rais Aziz (European Scientific Journal, ESJ, 2016)
Software requirements are one of the root causes of failure for IT software development projects. Reasons for this may be that the requirements are high-level, many might simply be wishes, or frequently changed, or they might be unclear, missing, for example, goals, objectives, strategies, and so on. Another major reason for projects’ failure may also be the use of improper techniques for software requirements specification. Currently, most IT software development projects utilise textual techniques like use cases, user stories, scenarios, and features for software requirements elicitation, analysis and specification. While IT software development processes can construct software in different programming languages, the primary focus here will be those IT projects using object-oriented programming languages. Object-oriented programming itself has several characteristics worth noting, such as its popularity, reusability, modularity, concurrency, abstraction and encapsulation. Object-oriented analysis and design transforms software requirements gathered with textual techniques into object-oriented programming. This transformation can cause complexity in identifying objects, classes and interfaces, which, in turn, complicates the object-oriented analysis and design. Because requirements can change over the course of a project and, likewise, software design can evolve during software construction, the traceability of software requirements with objects and components can become difficult. Apart from leading to project complexity, such a process can impact software quality and, in the worst-case scenario, cause the project to fail entirely. The goal of this article is to provide interface-driven techniques that will reduce ambiguity among software requirements, improve traceability and simplify software requirements modelling.